PENGARUH PENGETAHUAN AKUNTANSI, SKALA USAHA DAN UMUR USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI (Studi Kasus pada UMKM di Kecamatan Jebres, Kota Surakarta) - Budiman, Freddy Arief (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2022)
Accounting information has important benefits for the success of a business. Accounting information that produces financial reports can be a consideration for MSME actors in making decisions. The purpose of this study was to analyze (1) the effect of accounting knowledge on the use of accounting information (2) to analyze the effect of business scale on the use of accounting information (3) to analyze the effect of business age on the use of accounting information. The population in this study were 115 MSMEs in the culinary sector in Jebres District, Surakarta City. The sampling technique used in this study was purposive sampling method. The data analysis technique used in this research is classical assumption test, descriptive analysis, multiple linear analysis, determination coefficient test, partial test and simultaneous test. Based on the results of data analysis the effect of accounting knowledge on the use of accounting information obtained a positive coefficient and a significant effect. Business Scale on the use of accounting information obtained a negative coefficient and has no effect. Business age on the use of accounting information obtained a positive coefficient and has no effect. The suggestion in this study is to add other variables that affect the use of accounting information, to expand the object of research. Keywords: Accounting Knowledge, Business Scale, Age of Business.